Analysis of Dielectric Properties of Some Polar and Non-Polar Liquids - Yadav, Ranjit Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
The study of dielectric behavior of polar, non polar liquids and their binary mixtures at various temperatures is very interesting. In this article the values of dielectric constant of polar, non polar & their binary mixtures has been experimentally determined and study their properties at various temperatures 288k, 298k, 308k & 318 K. In this experiment the dielectric constant of the mixture of carbon tetra chloride - ethyl acetate and carbon tetra chloride – dimethyl ether was calculated at different temperatures in different concentrations. The results are discussed in the light of intermolecular interactions occurring in the binary mixture.